2023
DOI: 10.1021/acs.estlett.3c00318
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Generation from a Germicidal Ultraviolet Lamp with Peak Emission at 222 nm

Abstract: Recent interest in commercial devices containing germicidal ultraviolet lamps with a peak emission wavelength at 222 nm (GUV222) has focused on mitigating virus transmission indoors while posing a minimum risk to human tissue. However, 222 nm light can produce ozone (O 3 ) in air. O 3 is an undesirable component of indoor air because of health impacts from acute to chronic exposure and its ability to degrade indoor air quality through oxidation chemistry. In seven 4 h experiments, we measured the production of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
0
18
1
Order By: Relevance
“…More quantitative estimates of UV fluence rate and its relationship to O 3 generation are available in recent work by Peng et al . and Link et al Most experiments are carried out at full light intensity. For “low-light” experiments, the lamp emission is attenuated by several layers of plastic, achieving a factor of ∼5 reduction in intensity (determined by the reduction in the steady-state O 3 concentration, which is assumed to scale linearly with average UV fluence). , For the “O 3 -only” experiments, the light is left off, and O 3 is introduced via a Pen-Ray ozone generator, with a steady-state O 3 concentration matching that of the GUV 222 experiments (∼100 ppb).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More quantitative estimates of UV fluence rate and its relationship to O 3 generation are available in recent work by Peng et al . and Link et al Most experiments are carried out at full light intensity. For “low-light” experiments, the lamp emission is attenuated by several layers of plastic, achieving a factor of ∼5 reduction in intensity (determined by the reduction in the steady-state O 3 concentration, which is assumed to scale linearly with average UV fluence). , For the “O 3 -only” experiments, the light is left off, and O 3 is introduced via a Pen-Ray ozone generator, with a steady-state O 3 concentration matching that of the GUV 222 experiments (∼100 ppb).…”
Section: Methodsmentioning
confidence: 99%
“…The indirect estimation of the lamp intensity is a limitation of this work, but the agreement between modeled and measured ozone production (see Results and Discussion Section) indicates that it is reasonably accurate. More quantitative estimates of UV fluence rate and its relationship to O 3 generation are available in recent work by Peng et al 22 and Link et al 21 Most experiments are carried out at full light intensity. For "low-light" experiments, the lamp emission is attenuated by several layers of plastic, achieving a factor of ∼5 reduction in intensity (determined by the reduction in the steady-state O 3 concentration, which is assumed to scale linearly with average UV fluence).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated in a previous study the formation of O 3 from a GUV222 device, but here we have supplemented those observations with measurements of VOC and UFP byproducts. Compared to the PECO/PCO technologies, the UV-based technologies removed less of the challenging chemicals and produced less VOC byproducts.…”
Section: Discussionmentioning
confidence: 77%
“…One limitation of using 254 nm UV (GUV254) fixtures for air disinfection is that they are not safe for human exposure, so they are usually either mounted near the ceiling for upper room irradiation or used inside ventilation ducts. , Studies have shown that 222 nm lamps can be used for whole-room disinfection to inactivate airborne bacteria and viruses without harm to human skin and eyes. However, it has also been shown that GUV222 forms substantial ozone, which can react further in the indoor environment to form harmful pollutants like formaldehyde and PM 2.5 . …”
Section: Introductionmentioning
confidence: 99%